International dynamics of inflation expectations - Aleksei Netésunajev; Lars Winkelmann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
To what extent are US and Euro Area (EA) inflation expectations determined by foreign shocks? How do transmissions change during the great recession and European sovereign debt crisis? We address these questions with a flexible structural VAR model of weekly financial markets' inflation expectations and an index of commodity futures. For the identification of the model, we exploit the heteroscedasticity of the data. We propose instrument-type regressions to uncover the economic nature and origin of identified shocks. In line with the discussion about global inflation, we find that inflation expectations can be labeled global over short expectations horizons but local at long horizons. While large US macro shocks explain the strong drop in US and EA inflation expectations during the great recession, expectations shocks are the important driver from 2009 on.
Keywords: E31; F42; E52; 330; spillover; monetary policy; expectations shocks; financial crisis; identification through heteroskedasticity